Peningkatan Hasil Belajar Siswa Kelas X kecantikan dan SPA 2 pada Mata Pelajaran Dasar-dasar Kejuruan(Perawatan Wajah Tidak Bermasalah) Menggunakan Media Pembelajaran Berbasis Gamifikasi di SMK Negeri 27 Jakarta: Penelitian - Kartika Agustina; Sri Irtawidjajanti; Neneng Siti Silfi Ambarwati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to improve the learning outcomes of Grade X Beauty and Spa 2 students in the subject Basic Vocational Competencies, specifically on the topic Facial Treatment for Non-Problematic Skin, through the use of gamified learning media at SMK Negeri 27 Jakarta. The research method employed is Classroom Action Research (CAR) using the Kemmis and McTaggart model, implemented in three cycles. Each cycle consists of planning, action, observation, and reflection stages. Gamified platforms such as Wordwall, Kahoot, and Gimkit were utilized to enhance student engagement and motivation. The results showed a progressive improvement in students’ learning outcomes across all three cycles, covering cognitive, affective, and psychomotor domains.